KEY SUCCESS FACTOR GOOD GOVERNMENT GOVERNANCE SERTA PENGARUHNYA TERHADAP KINERJA PEMERINTAH (Survey pada Pemerintah Kabupaten Gunungkidul) - Handi Yuniar Lestiawan; Bambang Jatmiko (MAKSIMUM, 2015)
In this era, local government performance in Indonesia is weak because there are many abuse of authority everywhere, like corruption, collusion, and nepotism. Each of local government should apply the principles of good government governance in the government environtment, this is to improve performnace of local government. In this research good government governance principle contain transparancy, accountability, residents particpation, fairness, and responsibility. The purpose of this research is analyze dan explain the empirical evidence about the influence of transparancy, accountability, residents participation, fairness, and responsibility to the performance of local government. This research use primary data. Primary data derived from quistionnaire which share to employee of local government in Gunungkidul. This research involve 100 sample’s. The sample is determined by Slovin sampling method. Sample in this research derived from the employee of local government and Gunungkidul’s residents. Analitycal method use multiple regression. The result of this research is transparancy, accountability, and residents participation don’t have influence to the performance of local government, but fairness and responsibility have a positive and significant influence to the performance of local government.Keyword: Good Government Governance, performance of local government.